Drought Tolerance in Pinus halepensis Seed Sources As Identified by Distinctive Physiological and Molecular Markers - Taïbi, Khaled; del Campo, Antonio D.; Vilagrosa, Alberto; Bellés, José M.; López-Gresa, María Pilar; Pla, Davinia; Calvete, Juan J.; López-Nicolás, José M.; Mulet, José M. (Frontiers in Plant Science, 2017)
Drought is one of the main constraints determining forest species growth, survival and productivity, and therefore one of the main limitations for reforestation or afforestation. The aim of this study is to characterize the drought response at the physiological and molecular level of different Pinus halepensis (common name Aleppo pine) seed sources, previously characterized in field trials as drought-sensitive or drought-tolerant. This approach aims to identify different traits capable of predicting the ability of formerly uncharacterized seedlings to cope with drought stress. Gas-exchange, water potential, photosynthetic pigments, soluble sugars, free amino acids, glutathione and proteomic analyses were carried out on control and drought-stressed seedlings in greenhouse conditions. Gas-exchange determinations were also assessed in field-planted seedlings in order to validate the greenhouse experimental conditions. Drought-tolerant seed sources presented higher values of photosynthetic rates, water use efficiency, photosynthetic pigments and soluble carbohydrates concentrations. We observed the same pattern of variation of photosynthesis rate and maximal efficiency of PSII in field. Interestingly drought-tolerant seed sources exhibited increased levels of glutathione, methionine and cysteine. The proteomic profile of drought tolerant seedlings identified two heat shock proteins and an enzyme related to methionine biosynthesis that were not present in drought sensitive seedlings, pointing to the synthesis of sulfur amino acids as a limiting factor for drought tolerance in Pinus halepensis. Our results established physiological and molecular traits useful as distinctive markers to predict drought tolerance in Pinus halepensis provenances that could be reliably used in reforestation programs in drought prone areas.